Pola Pengobatan Pada Pasien Infark Miokard Akut Di Rumah Sakit Abdul Wahab Sjahranie Samarinda - Desta Winanda; Wisnu Cahyo Prabowo; Rolan Rusli (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
Acute myocardial infarction is a major health problem that needs special attention because of the mortality prevalence and costs is quite high. Generally caused by plaque rupture and thrombus of coronary arteries so that the oxygen-containing blood supply is reduced to the myocardium. The purpose of this study was to determine the characteristics of acute myocardial infarction patients and acutemiokardial infarction drug use pattern at Abdul Wahab Sjahranie Hospital, Samarinda City in the January-December 2018 period. This study was a non-experimental study with a retrospective method and analyzed descriptively. Sampling using a purposive sampling method. The results of the most characteristic study were obtained in patients with acute myocardial infarction in men, namely 7,4%, age characteristics 46-55 years 37,1%, private work 48,6%, and high school education 47,1%. The most treatment pattern used in STEMI patients out of 32 patients was Nitrate + DAPT + Anticoagulant + ACE-I + Statin for 6 patients (18.7%) and the most treatment pattern used in NSTEMI patients out of 38 patients was Nitrate + DAPT + Anticoagulant + ß-Blocker + Statins in 7 patients (18.4%). The use of most drugs ISDN (antiangina) as much as 90%, morphine and petidine (potency analgesic) 8.6%, aspirin (antiplatelet) 84.3%, fondaparinuks (anticoagulants) 68.6% and streptokinase (fibrinolytic agents) 5.7% . To prevent reinfarction the most used drug is bisoprolol (ß-Blocker) 28.6%. The most commonly used left ventricular damage inhibitor candesartan (ARB) is 22.8%. The most given antidislipidemia was simvastatin 47.1%.